Liver Stiffness Measurement in Psoriasis: Do Metabolic or Disease Factors Play the Important Role?. (23rd February 2016) - Pongpit, Jamrus; Porntharukchareon, Saneerat; Kaewduang, Piyaporn; Promson, Kwannapa; Stitchantrakul, Wasana; Petraksa, Supanna; Thakkinstian, Ammarin; Kositchaiwat, Chomsri; Rajatanavin, Natta; Sobhonslidsuk, Abhasnee
Abstract : Background . An increased prevalence of metabolic syndrome including nonalcoholic fatty liver disease (NAFLD) was reported in psoriasis. NAFLD can progress to nonalcoholic steatohepatitis and fibrosis. Transient elastography (TE) is a noninvasive liver fibrosis assessment. We evaluated the prevalence of significant liver fibrosis or high liver stiffness measurement (LSM) using the LSM cutoff over 7 kPa and its associated factors in psoriatic patients. Methods . Subjects underwent TE and ultrasonography. Univariate and multivariate analysis were performed for the associated factors. Results . One hundred and sixty-eight patients were recruited. Three patients were excluded due to TE failure. Mean BMI was 24.8 ± 4.7 kg/m 2 . NAFLD, metabolic syndrome, and diabetes were seen in 105 (63.6%), 83 (50.3%), and 31 (18.8%) patients. The total cumulative dose of methotrexate over 1.5 g was seen in 39 (23.6%) patients. Mean LSM was 5.3 ± 2.9 kPa. High LSM was found in 18 (11.0%) patients. Waist circumference (OR: 1.24; 95% CI: 1.11–1.38; P = 0.0002 ), diabetes (OR: 12.70; 95% CI: 1.84–87.70; P = 0.010 ), and AST (OR: 1.08; 95% CI: 1.02–1.16; P = 0.017 ) were associated with high LSM. Conclusion . 11% of psoriatic patients had significant liver fibrosis by high LSM. Waist circumference, diabetes, and AST level were the independent predictors.